Dinamika Pengambilan Keputusan dan Perkembangan Jiwa Wirausaha pada Mahasiswa - Aning Az Zahra; Aftina Nurul Husna; Ahmad Liana Amrul Haq (Psympathic : Jurnal Ilmiah Psikologi, 2019)
This study aims to describe the dynamics of entrepreneurial decision making and the development of entrepreneurial spirit in students who are self-employed. The researcher used phenomenology to understand the psychological dynamics in students who are self-employed. The results of the study are starting from the subject decision making of entrepreneurship is related to several factors, namely internal and external factors. Internal factors related to the desire to be independent to meet needs, want to help, like challenges and seek freedom. External factors related to family and other people. This research found that an entrepreneur must have a strong commitment and consistency towards his business. An entrepreneur should also have good interpersonal skills, this is important for building relationships. Even so, the entrepreneurial spirit in students still needs to be improved, especially on commitment, consistency, and decision making.